PENERAPAN INTELECTUAL INTELLIGENCE (IQ) AND SPIRITUAL INTELLIGENCE (SQ) CONTRIBUTIONTO THE EFFECTIVENESS OFLEADERSIP MODEL OF HEADMASTEROF SENIOR HIGH SCHOOL (SMA) IN KOTA BATU SARIAKIN* DAN ANWAR - Lain-lain, Sariakin dan (JURNAL SERAMBI ILMU, 2010)
Intellectual intelligence (IQ) and spiritual intelligence (SQ) is an energetic sourcewhich completes each other. Both contribute and ply an important role to theleadership model. Therefore, this research was conducted based on the fact that IQand SQ were needed to form an effective leadership model. In getting the quality ofeducation which tend to increase the uman quality in Indonesia especially in KotaBatu, it is also considered by headmaster as one of the main factors which influencesthe success of increasing education quality. This research is aimed to know how muchcontribution IQand SQ to the effectiveness of leadership model of the SMAheadmasters in Kota Batu.The population number of this research is 291 teachers ofSMA in Kota Batu. According to the krejcietable, there should be 165samples. Datacollection for the sample used the assessment instrument of IQ,SQ, and the leadershipmodel effectiveness used questionnaire. The analysis technique used is descriptive anddouble regression techniques.The result of the research shows that (1) there is asignificant positive correlation between the IQ and SQ to the headmaster's leadersipmodel with the contribution of 46.5%, (2) the IQ has a positive contribution to theleadership model effectiveness of SMA in Kota Batu as much as 21.39%, and (3) SQhas a positive contribution to the leadership model effectiveness of SMA in Kota Batuas much as 25.11%